OPTIMALISASI EKONOMI KREATIF DESA PADA MASA PANDEMI COVID 19 DI DESA RAGASMASIGIT KECAMATAN CARENANG KABUPATEN SERANG - Abdul Aziz; Mella Widiyati; Eka Assolehah Putri; Septhika Merdova; Muhadi Muhadi; Uun Uun (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
Creative optimization of Ragasmasigit Village, Carenang District, Serang Regency in the economic sector during the COVID-19 pandemic is very much needed in order to survive and compete for life. (a case study of the “Rice Rice husk” business group in Ragasmasigit Village, Carenang District, Serang Regency). Regarding the optimization, the village farmers are required to be able to prepare the best quality of rice at each harvest period, in order to produce quality rice waste. Currently, the people of Ragasmasigit Village are codifying rice husks taken from farmer mill waste into roasted rice husks, then given the latest innovations with the intention that rice husks have a higher selling power for consumers who love plants or others and are promoted through digital marketing (marketing). digital) in order to be better known to many consumers at the regional and even national level. With the implementation of an optimal village creative economy, there is great hope that it will reduce the number of unemployed and make the image of the village more competitive during the COVID-19 pandemic.